Delegation of Duties on Strategic Plan Implementation in County Government of Nakuru, Kenya (British Journal of Multidisciplinary and Advanced Studies, 2023)
Nakuru County Government has been facing the problem of poor state of county roads, shortage of water and strategic plan implementation in terms of attainment of goals, budgetary allocation to projects and timelines in project completion. The study sought to establish the effect of delegation of duties on strategic plan implementation in county government of Nakuru, Kenya. The study was anchored on implementation theory and theory of delegation, accountability and empowerment. A descriptive research design and census were used in the study. The target population was 107 employees in job group P and Q from the 11 ministries in the county. Quantitative data was analyzed using descriptive and inferential statistics with the help of Statistical Package for Social Sciences (SPSS) version 24. Qualitative data was analyzed using content analysis. Content validity of research instrument was determined through a pilot study. Principle Axis factoring method was used to test the construct validity of research instrument. Cronbach’s Alpha method was used to determine reliability of research instrument with the aid Statistical Package for Social Sciences. Data was presented in form of tables.  Findings indicated that there was a strong positive and significant effect of delegation of duties on strategic plan implementation. It was recommended that the county government should have a clear flow of communication between the various management levels. The study's results assist the county government and other policymakers identify major competitive forces in the environment and to develop methods to enhance performance, in order to facilitate project implementation.